Soil organic carbon dynamics in land-use systems in the tropical dry forest of Colombia - Andrade, Hernán J.; Greñas Corrales , Oscar Enrique; López Avellaneda , Paula Alejandra (Revista de Ciencias Agrícolas, 2025)
Soil organic carbon (SOC) is a crucial reservoir that facilitates climate change mitigation through its sequestration. The SOC stock was estimated in the top 30 cm in the predominant land use systems (LUS) (agriculture, grasslands, and forestry – forestry plantations, gallery forests, and natural regeneration) in the Centro Universitario Regional del Norte (CURDN), located in the dry zone of northern Tolima, Colombia. The bulk density (BD) and SOC concentration were estimated at this depth in a sampling. Information on the latter variable was also taken from a study in the same area in 2007. The effects of possible changes in land use on SOC stock between 2007 and 2021 were estimated, calculating a change rate between the two years. A significant effect of land use on the variables analyzed was found: agriculture presented the highest BD and lowest SOC concentration, while livestock production reached the highest SOC concentration and stock (1.45% and 63.2 Mg C/ha, respectively). The SOC stock, after 14 years, increased in all LUS, mostly in livestock production (150%), resulting in a SOC capture rate of 3.0 Mg/ha/year. Changing livestock to other uses can cause emissions of up to 60.6 Mg CO2/ha and up to 9.3 Gg CO2 in the total area of the CURDN. These results are the basis for LUS management for climate change mitigation through SOC conservation and sequestration.